Angiotensinogen and interleukin-18 as markers of chronic kidney damage in children with a history of hemolytic uremic syndrome - Lipiec, K; Adamczyk, P; Świętochowska, E; Ziora, K; Szczepańska, M (Physiological research, 2017)
Hemolytic uremic syndrome (HUS) is a type of thrombotic microangiopathy, in the course of which some patients may develop chronic kidney disease (CKD). It is clinically important to investigate the markers of a poor prognosis. The levels of angiotensinogen (AGT) and interleukin-18 (IL-18) in serum and urine were evaluated. Study was conducted in 29 children with a history of HUS. Serum and urine AGT concentration was significantly higher in children after HUS as compared to the control group. No differences depending on the type of HUS and gender were noted. The serum concentration of IL-18 in children after HUS was significantly lower, whereas in urine did not differ significantly between the sick and healthy children. A negative correlation between the concentration of AGT in serum and albuminuria in patients after HUS was detected. The results indicate that the concentration of AGT in serum and urine in children after HUS increases, which may indicate the activation of the intrarenal renin-angiotensin-aldosterone system. The statement, that AGT may be a good biomarker of CKD after acute kidney injury due to HUS requires prospective studies with follow-up from the acute phase of the disease on a larger group of patients. Reduced IL-18 serum concentration in children after HUS with no difference in its urine concentration may indicate a loss of the protective effects of this cytokine on renal function due to previously occurred HUS.
Keywords: interleukin-18; Infant; předškolní dítě; Humans; Interleukin-18; reprodukovatelnost výsledků; angiotensinogen; Sensitivity and Specificity; mužské pohlaví; hemolyticko-uremický syndrom; Kidney Failure, Chronic; Child, Preschool; Adolescent; Angiotensinogen; biologické markery; ženské pohlaví; lidé; senzitivita a specificita; mladiství; Reproducibility of Results; dítě; chronické selhání ledvin; Biomarkers; Child; Male; kojenec; Hemolytic-Uremic Syndrome; Female